SnFe2O4 Nanozyme Based TME Improvement System for Anti-Cancer Combination Thermoradiotherapy - Zeng, Wen; Liu, Chunping; Wang, Shuntao; Wang, Ziqi; Huang, Qinqin (Frontiers in Oncology, 2021)
High doses of radiotherapy (RT) are associated with resistance induction. Therefore, highly selective and controllable radiosensitizers are urgently needed. To address this issue, we developed a tin ferrite (SFO)-based tumor microenvironment (TME)-improved system (SIS) that can be used in combination with low-dose radiation. The SIS was delivered via intratumoral injection directly to the tumor site, where it was stored as a ration depot. Due to the photothermal properties of SFO, SIS steadily dissolved under near-infrared (NIR) laser irradiation. Simultaneously, the dual glutathione oxidase (GSH-OXD) and catalase (CAT) activities of the SFO nanozyme significantly lowered the content of GSH in tumor tissues and efficiently catalyzed the conversion of intracellular hydrogen peroxide to produce a large amount of oxygen (O2) for intracellular redox homeostasis disruption, thus reducing radiotherapy resistance. Our in vivo and in vitro studies suggested that combining the SIS and NIR irradiation with RT (2Gy) significantly reduced tumor proliferation without side effects such as inflammation. To conclude, this study revealed that SFO-based nanozymes show great promise as a catalytic, radiosensitizing anti-tumor therapy.